2011
DOI: 10.1016/j.wocn.2011.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Why are Korean tense stops acquired so early?: The role of acoustic properties

Abstract: Transcription-based studies have shown that tense stops appear before aspirated or lax stops in most Korean-acquiring children's speech. This order of mastery is predicted by the short lag Voice Onset Time (VOT) values of Korean tense stops, as this is the earliest acquired phonation type across languages. However, the tense stop also has greater motor demands than the other two phonation types, given its pressed voice quality (negative H1-H2) and its relatively high f0 value at vowel onset, word-initially. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 33 publications
(51 reference statements)
4
51
0
Order By: Relevance
“…In utilizing the two cues in perception, Schultz, Francis & Llanos (2012) have shown that English listeners put more perceptual weight on VOT than F0 in categorizing /b/ vs. /p/. Kong and Edwards (2011) provided additional supporting evidence drawn from eye-movement patterns to show that F0 was a secondary cue to English listeners since they relied on F0 only when VOT was ambiguous in differentiating /d/ from /t/.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In utilizing the two cues in perception, Schultz, Francis & Llanos (2012) have shown that English listeners put more perceptual weight on VOT than F0 in categorizing /b/ vs. /p/. Kong and Edwards (2011) provided additional supporting evidence drawn from eye-movement patterns to show that F0 was a secondary cue to English listeners since they relied on F0 only when VOT was ambiguous in differentiating /d/ from /t/.…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, Kong, Beckman & Edwards (2011) showed that young adult listeners tended to rely more on F0 than VOT in differentiating the lax stop /t/ from the aspirated stop /t h / when attempting to categorize the stop consonants spoken by adults and children into one of the three stop phonation types.…”
Section: Introductionmentioning
confidence: 95%
“…The special linguistic behavior of people born around 1970s and later can also be observed in another sound change underway in Korean. Recent studies have found that people born around that time are responsible for the merger of Voice Onset Time (VOT) between lenis and aspirated stops (Silva 2006, Wright 2007, Kang and Guion 2008, Kong, Beckman, and Edwards 2011, Oh 2011, Kang 2014. As mentioned earlier, Korean has a three-way laryngeal contrast in obstruents: lenis, aspirated, and tense.…”
Section: High-on-[il] and Vot Mergermentioning
confidence: 96%
“…The consonant-induced F0 difference extends far beyond the initial portion of the immediately following vowel indicating that the F0 perturbation is not an automatic consequence of physiological restrictions in laryngeal articulation (Jun, 1996;Kim, 2000;Silva, 2006). Recent perception studies also find that F0 is a crucial perceptual cue for stop distinction, for lenis-aspirated stops in particular (Kim et al, 2002;Kim, 2004;Lee and Jongman, 2011;Kong et al, 2011). So, this recent change in Seoul Korean is consistent with a process of tonogenesis, whereby consonant-induced F0 perturbation is exaggerated and reinterpreted by learners as a primary contrast, eventually replacing the original voicing or phonation contrast of consonants (Hombert et al, 1979;Kingston, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the stop production by children, ranging in age from 2 to 10 years, in Present Day Korean show that children produce a substantial overlap of VOT values between aspirated and lenis stops and more reliable difference in F0(Kim and Stoel-Gammon, 2009;Kong et al, 2011;Lee and Iverson, 2012) in line with younger adult speakers' speech pattern.…”
mentioning
confidence: 96%